First-Principles Molecular Dynamics and Computed Rate Constants for the Series of OH-HX Reactions (X = H or the Halogens): Non-Arrhenius Kinetics, Stereodynamics and Quantum Tunnel - Coutinho, Nayara D.; Aquilanti, Vincenzo; Sanches-Neto, Flávio O.; Vaz, Eduardo C.; Carvalho-Silva, Valter H. (Computational Science and Its Applications - ICCSA 2018, 2018)
This paper is part of a series aiming at elucidating the mechanisms involved in the non-Arrhenius behavior of the four-body OH + HX (X = H, F,Cl, Br and I) reactions. These reactions are very important in atmospheric chemistry. Additionally, these four-body reactions are also of basic relevance for chemical kinetics. Their kinetics has manifested non-Arrhenius behavior: the experimental rate constants for the OH + HCl and OH + H2 reactions, when extended to low temperatures, show a concave curvature in the Arrhenius plot, a phenomenon designated as sub-Arrhenius behavior, while reactions with HBr and HI are considered as typical processes that exhibit negative temperature dependence of the rate constants (anti-Arrhenius behavior). From a theoretical point of view, these reactions have been studied in order to obtain the potential energy surface and to reproduce these complex rate constants using the Transition State Theory. Here, in order to understand the non-Arrhenius mechanism, we exploit recent information from ab initio molecular dynamics. For OH + HI and OH + HBr, the visualizations of rearrangements of bonds along trajectories has shown how molecular reorientation occurs in order that the reactants encounter a mutual angle of approach favorable for them to proceed to reaction. Besides the demonstration of the crucial role of stereodynamics, additional documentation was also provided on the interesting manifestation of the roaming phenomenon, both regarding the search for reactive configurations sterically favorable to reaction and the subsequent departure of products involving their vibrational excitation. Under moderate tunneling regime, the OH + H2 reaction was satisfactory described by deformed-Transition-State Theory. In the same reaction, the catalytic effect of water can be assessed by path integral molecular dynamics. For the OH + HCl reaction, the theoretical rate coefficients calculated with Bell tunneling correction were in good agreement with experimental data in the entire temperature range 200–2000 K, with minimal effort compared to much more elaborate treatments. Furthermore, the Born-Oppenheimer molecular dynamics simulation showed that the orientation process was less effective than for HBr and HI reactions, emphasizing the role of the quantum tunneling effect of penetration of an energy barrier in the reaction path along the potential energy surface. These results can shed light on the clarification of the different non-Arrhenius mechanisms involved in four-body reaction, providing rate constants and their temperature dependence of relevance for pure and applied chemical kinetics.